RESEARCH OF THE COLD-BEATING GEAR HARDNESS ON THE BASIS OF MICROSTRUCTURE - LI YuXi; LI Yan; CUI LiMu; XIAO JiMing; CHEN YuZhao (Jixie qiangdu)
Hardness is the important factors to measure the quality of the gear. The gear processed by traditional technology has a lower tooth surface hardness because of the cut metal fibre. This article was based on copper,aluminum,steel Q235,for gear cold-beating. The gear organization change and its relationship with hardness distribution were researched on the basis of the material microstructure. In the experiment,the gear metal organization was not cut off after cold-beating,accompanying the crystal granular flow and the increasing dislocation density. Eventually,the gear organization was to be close strips fibrous tissue.It was found that the hardness and strength of the gear had a big enhancement after the two directions measurement of the tooth surface hardness distribution. This technology improved the processing surface organization and the overall quality of the gear.